Think small. The construction of imagined tradition in German "Land"-magazines. (December 2016) - Marley, Carol; Reershemius, Gertrud
Abstract: This article is the first linguistic analysis of a new category of lifestyle magazines in the German speaking countries, based on methods of corpus linguistics and multimodal discourse analysis. Since the launch of the magazine LandLust in Germany in 2005, more than twenty publications of so called "land magazines" have appeared on the market, attracting millions of readers. Our research analyses land magazines as discursive events. We examine the specific combination of discourses land magazines are serving or creating by looking at the semiotic practices – writing and images – they manifest themselves by. Our results show that the magazine under scrutiny does not simply provide new forms of escapism but also positions itself politically in subtle ways as part of the traditional-conservative spectrum by reacting to metalinguistic discourses such as purism and feminist criticism.